ANALISIS KOMPONENSIAL KESINONIMAN NOMINA BAHASA MELAYU JAMBI SEBERANG KELURAHAN TANJUNG RADEN - Siti Aisyah; Eddy Pahar Harahap (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2015)
The purpose of this study is to describe nouns synonymy Jambi Malay Village Opposite Tanjung Raden through componential analysis. The problem of this research is. How synonymy noun Malay Jambi Opposite the village of Tanjung Raden through componential analysis. These results indicate that the Malay language in Tanjung Raden Jambi there are words that are particularly synonymy berkesinoniman Noun. Given this research, it can be used as a guide for the speakers who are not native speakers of Malay Jambi in using word-word that shaped synonymy in Malay Jambi Opposite the village of Tanjung Raden, so there is no misunderstanding in wearing a sentence or speech